Nonadiabatic effects in the irradiation of ethylene - Wang, Zhi Ping; Dinh, Phuong Mai; Reinhard, Paul-Gerhard; Suraud, Eric; Zhang, Feng Shou (International Journal of Quantum Chemistry, 2011)
In the framework of the time-dependent local density approximation, applied to valence electrons, coupled nonadiabatically to molecular dynamics of ions, the irradiations of ethylene by laser and fast charged projectiles are studied. We find that the Coulomb fragmentation sensitively depends on the laser frequency and on the charge of the projectile. © 2010 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2023-07-24
Keywords: ethylene; irradiation; nonadiabatic effects; TDDFT-MD